2023
DOI: 10.1007/s10462-023-10442-2
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment analysis: A survey on design framework, applications and future scopes

Abstract: Sentiment analysis is a solution that enables the extraction of a summarized opinion or minute sentimental details regarding any topic or context from a voluminous source of data. Even though several research papers address various sentiment analysis methods, implementations, and algorithms, a paper that includes a thorough analysis of the process for developing an efficient sentiment analysis model is highly desirable. Various factors such as extraction of relevant sentimental words, proper classification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 243 publications
(333 reference statements)
0
9
0
Order By: Relevance
“…Its calculation is based on a combination of two metrics, one of which measures how many times a word appears in a collection of documents, and the other measures the word’s inverse document frequency. In a document, term frequency (TF) counts the number of times words appear, and inverse document frequency (IDF) is a method that helps distinguish and classify documents easily by giving importance or weightage to words that are unique to a certain set of documents [ 30 ]. Words in the document with high or low-frequency terms are given more weight by the IDF.…”
Section: Proposed Systemmentioning
confidence: 99%
“…Its calculation is based on a combination of two metrics, one of which measures how many times a word appears in a collection of documents, and the other measures the word’s inverse document frequency. In a document, term frequency (TF) counts the number of times words appear, and inverse document frequency (IDF) is a method that helps distinguish and classify documents easily by giving importance or weightage to words that are unique to a certain set of documents [ 30 ]. Words in the document with high or low-frequency terms are given more weight by the IDF.…”
Section: Proposed Systemmentioning
confidence: 99%
“…The significant works done for aspect term extraction and aspect-based sentiment analysis in general and in the Hindi language are discussed in the literature survey (3)(4)(5)(6)(7)(8) . Md Shad Akhtar et al (9) reported the first supervised approach to the aspect term extraction task; they created an annotated dataset of high quality and built a machine learning model for sentiment analysis to show practical usage of the dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Sentiment analysis In product design, sentiment analysis plays a crucial role in identifying customers' emotional attitudes towards a product and classifying them as positive, negative, or neutral. Sentiment analysis can be conducted at three different levels [141][142][143] : (i) document-level, which is a coarse-grained analysis of all reviews in a document; (ii) sentence-level, which is a medium-grained analysis of individual sentences; and (iii) aspect (attribute)-level, which is a fine-grained analysis of specific product attributes.…”
Section: Data Processingmentioning
confidence: 99%